Good Character: the role of counseling teacher in establishing student discipline character in madrasah - Hasibuan, Nurmiah; Hasibuan, Ali Daud; Mahidin, Mahidin (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
In Indonesia, students and teachers often engage in disciplinary behaviour. Discipline is the only educational characteristic that needs to be emphasized in schools. Most students have not shown good disciplinary character, where students are not on time to enter class during study hours, like to skip class during learning, and do not do assignments so the character of poor student discipline becomes a habit. This study aims to determine the role of the guidance and counselling teacher in the formation of the disciplinary character of students at MTS Al Washliyah. The research method used in this study is descriptive qualitative which examines the role of guidance and counseling teachers in the formation of students' disciplinary character. The data were collected through interviews, document analysis, focused discussions, and observations as outlined in field notes. The results of this study indicate that the role of the guidance and counselling teacher in the formation of the disciplinary character of students is going quite well. Guidance and counselling teachers collaborate with student representatives, homeroom teachers, and parents to solve the problems of students who lack discipline. Students who lack discipline are given individual counselling services and guidance and counselling teachers also make visits to students' homes to find out the factors causing these students to lack discipline and to discuss student problems at school with students' parents. The findings of this study are the role of guidance and counselling teachers in shaping the disciplinary character of students in MTS Al Washliyah.